2014
DOI: 10.1248/bpb.b14-00373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administering Sodium Selenite, Methylseleninic Acid, and Seleno-L-methionine on Glucose Tolerance in a Streptozotocin/Nicotinamide-Induced Diabetic Mouse Model

Abstract: The effects of administering the selenocompounds, sodium selenite, methylseleninic acid (MSA), and seleno-L-methionine (SeMet) on glucose tolerance were compared in the nicotinamide (NA) and streptozotocin (STZ)-induced diabetic mouse model. ICR mice were intraperitoneally treated twice with STZ (100 mg/ kg) 15 min after an injection of NA (120 mg/kg) at a 1-d interval. Non-fasting blood glucose levels were then monitored weekly while orally administering the selenocompounds at 158 µg Se/kg body weight with fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…32,33) Although supplementary SeMet significantly decreased plasma insulin levels in HFD groups, it had no effect for OGTT blood glucose level in HFD induced-insulin resistance. This suggests that SeMet has an insulin-mimetic action as described previously, 31) but its action may not be as significant as the suppression of blood glucose occurs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…32,33) Although supplementary SeMet significantly decreased plasma insulin levels in HFD groups, it had no effect for OGTT blood glucose level in HFD induced-insulin resistance. This suggests that SeMet has an insulin-mimetic action as described previously, 31) but its action may not be as significant as the suppression of blood glucose occurs.…”
Section: Discussionmentioning
confidence: 52%
“…30) These reports are inconsistent with our results, but the effect of supplementary Se on glucose tolerance or insulin resistance may be dependent on the dosage and the bioavailability of selenocompounds described previously. 27,31) The high Se dosage is reported to exacerbate insulin resistance of diabetic mouse models. 32,33) Although supplementary SeMet significantly decreased plasma insulin levels in HFD groups, it had no effect for OGTT blood glucose level in HFD induced-insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Selenocompound metabolism was predicted to increase by treatment with SB through PICRUSt analysis based on the 16S rRNA sequences. Selenocompounds influence diabetes through energy metabolism and oxidative stress in pancreatic islets (21,40,41). One study investigated the effects of selenocompounds on diabetes by using a nicotinamide and STZ-induced diabetes mouse model.…”
Section: E58mentioning
confidence: 99%
“…33) We previously reported that SeMet exhibited the highest bioavailability of the 3 selenocompounds supplemented under insufficient Se status, particularly in the pancreatic Se content and GPX1 activity. 24) However, as shown in Figs. 4 and 5, insulin density was not restored by SeMet ingestion, whereas 8-OHdG density in pancreatic islets significantly decreased with supplementation.…”
Section: Discussionmentioning
confidence: 91%
“…24) Briefly, ICR mice (10 mice/group) were fasted for 16 h and then intraperitoneally treated twice with 100 mg/kg STZ 15 min after an injection of 120 mg/kg NA at a 1-d interval. The next day, mice were orally administered 158 µg Se (2 µmol)/kg/d SeMet for 5 weeks with ad libitum access to sterilized water and a γ-rayirradiated torula yeast-based diet (32.3±2.92 ng Se/g) as a Sedeficient diet.…”
Section: Methodsmentioning
confidence: 99%